Multi-disciplinary and shared decision-making approach in the management of organ-confined prostate cancer - Syed M. Nazim (Taylor & Francis Group, 2018)
Decision-making in the management of organ-confined prostate cancer is complex as it is based on multi-factorial considerations. It is complicated by a multitude of issues, which are related to the patient, treatment, disease, availability of equipment(s), expertise, and physicians. Combination of all these factors play a major role in the decision-making process and provide for an interactive decision-making preferably in the multi-disciplinary team (MDT) meeting. MDT decisions are comprehensive and are often based on all factors including patients’ biological status, disease and its aggressiveness, and physician and centres’ expertise. However, one important and often under rated factor is patient-related factors. There is considerable evidence that patients and physicians have different goals for treatment and physicians’ understanding of their own patients’ preferences is not accurate. Several patient-related key factors have been identified such as age, religious beliefs, sexual health, educational background, and cognitive impairment. We have focused on these areas and highlight some key factors that need to be taken considered whilst counselling a patient and understanding his choice of treatment, which might not always be match with the clinicians’ recommendation. Keywords: Prostate cancer, Decision-making, Multi-disciplinary team (MDT), Patients’ preferences